The role of scientific knowledge in Extinction Rebellion's communication of climate futures - Karnik Hinks, Ella; Rödder, Simone (Frontiers in Communication, 2023)
Introduction Extinction Rebellion (XR) is one of the central players in climate movements in the United Kingdom. Considering the historical relationship that environmentalists have had with science and scientific knowledge, we examine the current treatment of science in the narrative put forward by XR United Kingdom. Methods Using mixed qualitative methods, the group's online press releases for the year 2019 were analysed, alongside fieldwork from 2 weeks spent at the United Nations' climate conference in Glasgow in 2021. The fieldwork data consists of participant observation combined with semi-structured interviews. Results The movement's demand to “tell the truth” utilises a narrative established on a fact-based enlightenment. This is complemented by notions of a fixed temporal deadline and predicted societal collapse. We highlight prominent perspectives that came to light and identify three main positions that the activists held with respect to science. Discussion The findings show the positioning of science and scientific knowledge as a supreme authority, which acts to depoliticize the discourse and induces reductionism in imagining climate futures. This positioning, combined with the centrality of apocalyptic imagery, hampers the construction of alternative futures and fails to engage meaningfully with climate justice.